Development of mobile-based learning in Kapita Selekta Pendidikan courses - Nurdaiman Nurdaiman; Nurhikmah H; Citra Rosalyn Anwar (Inovasi Kurikulum, 2024)
This research is development research that focuses on creating mobile learning-based learning media in education courses. This research aims to produce mobile learning-based learning media using the Smart Apps Creator (SAC) application that suits student needs and is valid and practical so students can learn anytime and anywhere. The research method used is Research and Development with the ADDIE development model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. This research was conducted at the Educational Technology Study Program, Faculty of Education in Universitas Negeri Makassar. This research found that mobile learning-based learning media in capita selecta education courses were developed and were in the valid category; analysis of the level of practicality of lecturer and student responses was in the excellent category, so a value was obtained in the practical category. Research into developing mobile learning-based learning media in capita selecta education courses is expected to make it easier for students to learn independently.   Abstrak Penelitian ini merupakan penelitian pengembangan yang berfokus pada pembuatan media pembelajaran berbasis mobile learning pada mata kuliah kapita selekta pendidikan. Penelitian ini bertujuan untuk menghasilkan media pembelajaran berbasis mobile learning dengan menggunakan aplikasi Smart Apps Creator (SAC) yang sesuai dengan kebutuhan mahasiswa yang valid dan praktis sehingga mahasiswa dapat belajar kapan saja dan di mana saja. Metode penelitian yang digunakan yaitu Research and Development dengan model pengembangan ADDIE yang terdiri dari 5 tahapan, yakni: analisis, desain, pengembangan, implementasi dan evaluasi. Penelitian ini dilaksanakan di Program Studi Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Makassar. Berdasarkan penelitian tersebut diperoleh media pembelajaran berbasis mobile learning pada mata kuliah kapita selekta pendidikan yang dikembangkan dan berada pada kategori valid; analisis tingkat kepraktisan respons dosen dan mahasiswa berada pada kategori sangat baik, sehingga diperoleh nilai dengan kategori praktis. Penelitian pengembangan media pembelajaran berbasis mobile learning pada mata kuliah kapita selekta pendidikan diharapkan dapat memudahkan mahasiswa dalam belajar secara mandiri. Kata Kunci: Media pembelajaran; mobile learning; SAC: Smart Apss Creator